Intracellular Processing of Human Herpesvirus 6 Glycoproteins Q1 and Q2 into Tetrameric Complexes Expressed on the Viral Envelope - Akkapaiboon, Pilailuk (American Society for Microbiology, 2004)
Human herpesvirus 6 (HHV-6) glycoproteins H and L (gH and gL, respectively) and the 80-kDa form of glycoprotein Q (gQ-80K) form a heterotrimeric complex that is found on the viral envelope and that is a viral ligand for human CD46. Besides gQ-80K, the gQ gene encodes an additional product whose mature molecular mass is 37 kDa (gQ-37K) and which is derived from a different transcript. Therefore, we designated gQ-80K as gQ1 and gQ-37K as gQ2. We show here that gQ2 also interacts with the gH-gL-gQ1 complex in HHV-6-infected cells and in virions. To examine how these components interact in HHV-6-infected cells, we performed pulse-chase studies. The results demonstrated that gQ2-34K, which is endo-β-N-acetylglucosaminidase H sensitive and which is the precursor form of gQ2-37K, associates with gQ1-74K, which is the precursor form of gQ1-80K, within 30 min of the pulse period. After a 1-h chase, these precursor forms had associated with the gH-gL dimer. Interestingly, an anti-gH monoclonal antibody coimmunoprecipitated mainly gQ1-80K and gQ2-37K, with little gQ1-74K or gQ2-34K. These results indicate that although gQ2-34K and gQ1-74K interact in the endoplasmic reticulum, the gH-gL-gQ1-80K-gQ2-37K heterotetrameric complex arises in the post-endoplasmic reticulum compartment. The mature complex is subsequently incorporated into viral particles.